PENGARUH GAYA KEPEMIMPINAN, DISIPLIN KERJA DAN PENGEMBANGAN KARIR TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT BATAM BAHARI SEJAHTERA - Jurnal Akuntansi Barelang (LPPM Universitas Putera Batam, 2017)
Human resource is one of important element in the organization, because human resources are the main driving force in the achievement of organization’s goals. Organization as a system will involve a variation of resources and those resources are related to one another. But, there are many factors that can degrade productivity, such as style of leadership, work discipline and career development. PT Batam Bahari Sejahtera has issues of style of leadership, work discipline and career development that can influence employee productivity. The main objectives of this research are developed to determine the effect of style of leadership on employee productivity, the effect of work discipline on employee productivity and the effect of career development on employee productivity at PT Batam Bahari Sejahtera. The hypothesis of this research are style of leadership has significant effect on employee productivity (H1), work discipline has significant effect on employee productivity (H2), career development has significant effect on employee productivity (H3), style of leadership, work discipline and career development together have significant effect on employee productivity (H4). In this quantitative causality research, data are collected using questionnaires. This research designed by using multiple linear regression analysis. The population are employees of PT Batam Bahari Sejahtera in Batam city. The sample in this research is 127 respondents based formula Slovin. Samples taken in this study is using simple random sampling technique. The analysis shows that style of leadership has significant effect on employee productivity (Ha1 accepted), work discipline has significant effect on employee productivity (Ha2 accepted), career development has significant effect on employee productivity (Ha3 accepted), style of leadership, work discipline and career development together have significant effect on employee productivity (Ha4 accepted).